The relationship between cultural awareness and participation in intercultural societal challenge - Winda Wulandari; Iis Sujarwati (Universitas Negeri Semarang, 2025)
Student engagement with intercultural societal challenges is investigated for academic programs as the globalizing trend requires students to interact effectively in multicultural settings, yet not all students are capable of doing this. Through explanatory sequential mixed methods, with quantitative data using questionnaires and qualitative data using semi-structured interviews, this study aims to investigate the interplay between cultural awareness and participation in the programs and to findout the challenges. The respondents were seventy-three students who ever followed this program in face-to-face or online meetings. To complete the qualitative data, semi-structured interviews with four students were used. The study revealed that enhanced cultural awareness levels directly influenced student enrollment in intercultural societal challenges. Students involved in the program discussed multiple challenges which included problems with language learning associated with cultural communication issues and differences in understanding between participants. This study both adds to existing academic documents because it demonstrates how cultural understanding drives students to actively participate in international programs, thus demonstrating why formalized cultural competence training should be integrated into university learning. This study brings originality through its examination of experiential intercultural program learning which enhances student adaptability and cross-cultural communication abilities in order to fill knowledge gaps in theoretical cultural awareness research.